THE STUDY ISSUES ON EDUCATION SYSTEM OF THE KOKAND KHANATE IN THE WORKS OF RUSSIAN ORIENTALISTS IN THE SECOND HALF OF 20th CENTURY (American Journal of Interdisciplinary Research and Development, 2024)
The article analyzes the works of Russian orientalists who made a significant contribution to the study of the education system in Kokand Khanate. In the research also shown that the moment there is no reason to assert that all studies conducted at various socio-political stages provided an objective assessment of the activities of the main stages of the traditional education system as schools and madrassahs in Kokand Khanate.